Efficient Ag@AgCl cubic cage photocatalysts profit from ultrafast plasmon-induced electron transfer processes - Tang, Yuxin (2014)
Photon-coupling and electron dynamics are the key processes leading to the photocatalytic activity of plasmonic metal-semiconductor nanohybrids. To better utilize and explore these effects, a facile large-scale synthesis route to form Ag@AgCl cubic cages with well-defined hollow interiors is carried out using a water-soluble sacrificial salt-crystal-template process. Theoretical calculations and experimental probes of the electron transfer process are used in an effort to gain insight into the underlying plasmonic properties of the Ag@AgCl materials. Efficient utilization of solar energy to create electron-hole pairs is attributed to the significant light confinement and enhancement around the Ag/AgCl interfacial plasmon hot spots and multilight-reflection inside the cage structure. More importantly, an ultrafast electron transfer process (≤150 fs) from Ag nanoparticles to the AgCl surface is detected, which facilitates the charge separation efficiency in this system, contributing to high photocatalytic activity and stability of Ag@AgCl photocatalyst towards organic dye degradation.